2017
DOI: 10.1021/acssuschemeng.7b02175
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Encapsulated Self-Assemblies of Ultrasmall Rhenium Nanoparticles: Catalysis and SERS Applications

Abstract: Ultrafast formation of stable and self-assembled rhenium (Re) nanoparticles (NPs) using a poly allylamine hydrochloride (PAH) scaffold within 120 s of wet-chemical reaction at room temperature in aqueous solution has been reported. The average diameters of the two different sets of Re NPs synthesized are ∼0.7 ± 0.25 and ∼1.7 ± 0.3 nm, which can be easily achieved by controlling the polymer to Re7+ molar ratio. The small-size Re NPs are formed in solution, self-assembled together to form the chain-like or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…It can be concluded that changes in the Tauc-plot indicate that the Re NPs dominates the UV-Vis spectrum. The band gap energy values obtained are also compatible with the literature [34,41,42]. It was found that the absorption spectra of Re/ReO 3 mixture and pure ReO 3 NPs were varied within the range from ultraviolet region to infrared region in spectrum depending on the synthesis parameters.…”
Section: Resultssupporting
confidence: 88%
“…It can be concluded that changes in the Tauc-plot indicate that the Re NPs dominates the UV-Vis spectrum. The band gap energy values obtained are also compatible with the literature [34,41,42]. It was found that the absorption spectra of Re/ReO 3 mixture and pure ReO 3 NPs were varied within the range from ultraviolet region to infrared region in spectrum depending on the synthesis parameters.…”
Section: Resultssupporting
confidence: 88%
“…1d). It is found that the absorbance of reaction solution after 2 h reaches equilibrium, indicating that the reduction of NH 4 ReO 4 can be accomplished in 2 h. The obtained Re NCs show no surface plasmon resonance (SPR) maximum probably due to the low dielectric constant,42 but have obvious absorbance from the UV to the NIR region (Fig. 1e and S3†).…”
Section: Resultsmentioning
confidence: 94%
“…Kundu et al [174] developed new Re-based catalysts on PAH scaffolds by reduction of NH 4 ReO 4 with NaBH 4 . The catalytic rate of 1.52 × 10 −1 min −1 was achieved for the reduction of 4-NA, which is the highest ever reported.…”
Section: Rhenium-based Nanocompositesmentioning
confidence: 99%
“…Reproduced with permission from Ref. [174] Copyright 2017 American Chemical Society abundant surface-active hot spots for SERS, and were used to detect MB. It showed that in the synthesis process, as the PAH concentration decreased from 1% to 0.5% the mean size of ReNPs increased (see Fig.…”
Section: Rhenium-based Nanocompositesmentioning
confidence: 99%